Evolution from Telescoping to Bending: An Origami-Inspired Flexible Bending Actuator - Zhaowen Shao; Wentao Zhao; Zhaotian Zuo; Jun Li (Applied Bionics and Biomechanics)
Soft actuators have great potential in human–machine interaction and soft robotics innovation. Origami exhibiting outstanding structural and topological properties can be a paradigm for people to design various soft robots. Inspired by origami, we have previously designed a telescopic actuator with excellent performance, mainly large force output, and two-way working. Although significant advances have been made in soft bending actuators, their further study and applications are limited due to small force output in a monotonous work style. In this paper, we design a series of novel bending actuators that inherit our prior telescopic actuator’s excellent characteristics to diversify soft actuators’ motion forms. Several actuators of different sizes are fabricated using three different materials and evaluated on a designed test platform. The test results show that actuators of different sizes using different materials perform differently. Namely, the maximum tip force produced by an actuator reaches 9.6 N, and the maximum bending angle is achieved by another one up to 138°. Finally, extensive demonstrations and tests include wriggling, gripping, and bidirectional motion in the water. They show our flexible bending actuators’ distinguishing characteristics of large output force and two-way working.